2016
DOI: 10.1007/s00380-016-0816-z
|View full text |Cite
|
Sign up to set email alerts
|

Late gadolinium enhancement on cardiac magnetic resonance predicts coronary vasomotor abnormality and myocardial lactate production in patients with chronic heart failure

Abstract: Myocardial fibrosis and microvascular dysfunction are key determinants of outcome in heart failure (HF); we examined their relationship in patients with HF. Our study included 61 consecutive patients with HF but without coronary stenosis. All underwent gadolinium-enhanced cardiac magnetic resonance to evaluate late gadolinium enhancement (LGE) and an acetylcholine (ACh) provocation test to evaluate microvascular dysfunction. During the ACh provocation test, we sampled blood simultaneously from the coronary sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 55 publications
(40 reference statements)
0
6
0
Order By: Relevance
“…One hundred fifty‐five articles received a complete review, and 56 studies met inclusion criteria and were included in the meta‐analysis (Figure 2 ). 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , …”
Section: Resultsmentioning
confidence: 99%
“…One hundred fifty‐five articles received a complete review, and 56 studies met inclusion criteria and were included in the meta‐analysis (Figure 2 ). 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , …”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, ACh-provoked coronary vasomotor abnormality (e.g. epicardial coronary spasm or microvascular spasm) in our previous study was shown to be closely associated with myocardial fibrosis (expressed as late gadolinium enhancement in cardiac MRI) in patients with heart failure and without organic coronary artery stenosis [ 111 , 112 ]. Coronary vasomotor abnormalities such as coronary spasm or microvascular spasm could affect the development of nonobstructive CAD, and might also be associated with LV dysfunction and heart failure [ 4 , 19 , 54 , 113 117 ].…”
Section: Significance Of the Ach Spasm Provocation Test In Left Ventrmentioning
confidence: 99%
“…Recently we reported endothelium dependent microvascular dysfunction correlate with cardiac fibrosis in HF patients without coronary artery stenosis [16]. Therefore, we examined the relationship between CFR as a marker of endothelium independent microvascular function and cardiac fibrosis in this study.…”
Section: Discussionmentioning
confidence: 95%
“…Several studies have shown that the presence of late gadolinium enhancement (LGE) by cardiac magnetic resonance (CMR) indicates myocardial fibrosis, predicting an increased risk of cardiovascular events and poor prognosis in patients with non-ischemic heart failure [14,15]. Recently, we reported that endothelial dependent microvascular dysfunction would worsen heart failure condition, especially with fibrotic myocardium [16].…”
Section: Introductionmentioning
confidence: 99%